Does acute coronary syndrome impact on the incidence of thrombosis after the implantation of an Absorb bioresorbable vascular scaffold? - Yohei Sotomi (2018)
© Europa Digital & Publishing 2017. All rights reserved. Aims: In the drug-eluting stent (DES) era, patients with acute coronary syndrome (ACS) had a higher risk of early stent thrombosis compared with stable patients. The present study aimed to evaluate whether the same is true for the bioresorbable vascular scaffold (BVS) (Abbott Vascular, Santa Clara, CA, USA). Methods and results: We assessed the relationship between the incidence of definite/probable scaffold thrombosis (ScT) (overall ScT and early ScT) and ACS percentage with the latest publications, including the most recent large randomised controlled trials. Out of a total study population of 13,708 devices in 45 trials, overall ScT was observed in 185 devices (1.35%) at a weighted mean follow-up period of 9.4 months, while early ScT was reported in 125 devices (0.97%) out of 12,896 devices in 44 trials. Meta-regression analysis demonstrated no significant correlation between overall/early ScT and the percentage of patients with ACS (overall ScT: R2=0.030, p=0.255; early ScT: R2=0.067, p=0.090). Conclusions: ACS appeared to have little impact on the incidence of ScT after the implantation of BVS. Further clinical study is warranted to investigate the predictors of ScT using multivariate analysis with sufficient statistical power.